2017
DOI: 10.1111/rda.13078
|View full text |Cite
|
Sign up to set email alerts
|

Prostate vascular flow: The effect of the ejaculation on the power doppler ultrasonographic examination

Abstract: Power Doppler sonography (PD) can accurately depict tissue perfusion, recognize slow flows, and is relatively angle independent. The monitoring of local blood flow by Doppler ultrasonography is helpful in differentiating prostatic physio-pathological conditions, but the recognizing of physiological variables that could affect it is crucial to apply this technique in clinical practice. This study aimed to evaluate if ejaculation affects blood flow to the prostate and to state how long this effect lasts. Serial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In clinical veterinary practice, the most commonly used methods to diagnose canine prostatic gland diseases are digital rectal examination and abdominal ultrasound (Mantziaras et al, 2017;Mukaratirwa & Chitura, 2007;Newell et al, 1998). Recently some authors suggested that the monitoring of local blood flow by Doppler or Contrast-Enhanced UltraSonography (CEUS) is helpful in differentiating prostatic physio-pathological conditions (Alonge, Melandri, Fanciullo, Lacalandra, & Aiudi, 2017;Bigliardi & Ferrari, 2011;Russo, Vignoli, & England, 2012;Troisi et al, 2015). Cytological evaluation by fine-needle aspiration or biopsy of the prostate is usually performed to confirm the benign nature of the prostate volume enlargement (Davidson & Baker, 2009;Kraft, Brown, & LeRoy, 2005;Levy et al, 2014;Paclikova, Kohout, & Vlasin, 2006).…”
mentioning
confidence: 99%
“…In clinical veterinary practice, the most commonly used methods to diagnose canine prostatic gland diseases are digital rectal examination and abdominal ultrasound (Mantziaras et al, 2017;Mukaratirwa & Chitura, 2007;Newell et al, 1998). Recently some authors suggested that the monitoring of local blood flow by Doppler or Contrast-Enhanced UltraSonography (CEUS) is helpful in differentiating prostatic physio-pathological conditions (Alonge, Melandri, Fanciullo, Lacalandra, & Aiudi, 2017;Bigliardi & Ferrari, 2011;Russo, Vignoli, & England, 2012;Troisi et al, 2015). Cytological evaluation by fine-needle aspiration or biopsy of the prostate is usually performed to confirm the benign nature of the prostate volume enlargement (Davidson & Baker, 2009;Kraft, Brown, & LeRoy, 2005;Levy et al, 2014;Paclikova, Kohout, & Vlasin, 2006).…”
mentioning
confidence: 99%
“…In dogs, it was recently reported that ejaculation induces an increase in the vascularisation of the prostate gland [34][35][36][37]. Augmented prostatic vascular flow can be detected up to 24 h after ejaculation by Power Doppler [34], which is very accurate for slow flows [36].…”
Section: Discussionmentioning
confidence: 99%
“…It can be hypothesized that, as reported in human medicine regarding PSA [20], during its transportation, CPSE can enter into the systemic circulation and its increase might be due to a CPSE wash-back into the bloodstream. Particularly, while pelvic muscles and peri-prostatic tissue contractions of ejaculation may increase the leakage of PSA [31] and CPSE into the bloodstream, the increased vascular bed revealed at the ultrasonographic examination [34,35] drives the biomarkers to the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The increased vascular prostatic flow is detectable up to 24 hr after ejaculation by Power Doppler (Alonge et al., ), which is very accurate in recognizing slow flows (Zelli et al., ). Pulsed‐Wave, more specific for high flows, is instead altered for at least 6 hr.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone, promoting androgenic‐receptor‐mediated tissue growth and stimulating angiogenesis and vascular growth (Franck‐Lissbrant, Haggstrom, Damber, & Bergh, ), must be considered among parameters possibly affecting prostatic vascularization. In the recent past, the role of ejaculation on prostatic vascular appearance on Power Doppler exam was assessed (Alonge, Melandri, Fanciullo, Lacalandra, & Aiudi, ) in order not to misdiagnose the prostatic neovascularization occurring during glandular disorders (Freitas et al., ; Newell et al., ; Polisca et al., ; Zelli et al., ). The present study aimed to evaluate whether and how ejaculation and blood testosterone affect prostatic Pulsed‐Wave exam and to state how long this effect lasts.…”
Section: Introductionmentioning
confidence: 99%